Strategic marketing management cases - Cravens, David W. (McGraw-Hill, 1998)
Strategic Marketing Management Cases is a versatile collection of approximately 45 cases. This casebook has a decision-making focus and addresses the challenges facing marketing managers today. It is organized to reflect the priorities of a marketing manager: market orientation, growth strategies and target market strategies.